TOPLUM-BİREY-CİNNET ÜÇGENİ VE BÖCEKLEŞEN YAŞAMLAR: TOPLUM BÖCEĞİ - Bulut, Sibel (Fırat University, 2019)
Bireyin toplumla çatışması ve bu çatışma sebebiyle yaşanan trajik hal ve olaylar edebiyatın en çok tekrarlanan meselelerinden biridir. Kerem Işık, Haldun Taner Öykü Ödülünü kazandığı ikinci öykü kitabı Toplum Böceği’nde aynı çatışmayı konu edinmiştir. Çocukluktan yetişkinliğe dek toplumun çizdiği sınırlar içinde, onun kurallarına uyumlu, kendine biçilen eğitim hayatı, kariyer planı, ideal evlilik yaşamı gibi aşamaları gerçekleştirmeye mecbur bırakılan bireylerin yaşadığı bunalım bu kitaptaki öykülerin odak noktasını oluşturmaktadır. Topluma uyum sağlamakta zorlanan bireylere biçilen son cinnettir. Cinnetin yarattığı trajik değişim/dönüşüm süreci ise Dostoyevski’ye, Kafka’ya öykünen bir böcekleşme durumuyla yansıtılmıştır. Yazar, dil oyunlarıyla süslediği mizahi, ironik anlatımıyla toplumun cenderesine sıkışmış bireylerin küçüldükçe küçülen yaşamlarını kurgu dünyasına taşımıştır. Çalışmamız kapsamında söz konusu eseri oluşturan öyküler toplum-birey-cinnet üçgeni üzerinden irdelenecek ve bireylerin değersizleşen böceksi yaşamı tartışılacaktır.

The conflict between the society and individuals and the tragic events of this conflict are one of the most important issues of literature. Kerem Işık has dealt with the same conflict in the her the second short story book Society Bug.which is Haldun Taner Short Story Award. In this book, the focus of the stories is the depression experienced by individuals who are compelled to realize the stages of society within the limits drawn by society, from childhood to adulthood, according to her rules, her educational life, career plan and ideal marriage life. The end of the individuals who have difficulty in adapting to society is the state of insanity. The tragic change / metamorphosis process caused by insanity is reflected in Dostoevsky's situation of insectism that emulates Kafka. The author, with the humorous and ironic expression he adorned with the language plays, reduced their diminished lives to the fiction world as the individuals who were trapped in the jeep of the society shrank. Within the scope of our study, the stories that within the work in question will be examined through the triangle of society-individual-insanity and the worthlessness of the individuals will be discussed.
Socıety-Individual-Gender Triangle and Life as an Insect:Toplum Böceği